2020
DOI: 10.1111/echo.14859
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic parameters associated with recovery in heart failure with reduced ejection fraction

Abstract: Objective: The study aims to determine the clinical and echocardiographic parameters of patients with recovered heart failure (HFrecEF). Methodology: Sixty-seven patients (cases) were identified as heart failure with recovered ejection fraction (HFrecEF), defined as improvement in EF ≥ 10%. Sixtynine patients (controls) were randomly selected by convenience sampling with no or <10% improvement in EF (HFrEF non-recovered). Results: The mean interval between baseline and follow-up echocardiography was 10.5 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
8
1
1
Order By: Relevance
“…No additional studies were added through the manual search. Therefore, a total of 18 studies were included in the meta-analysis [ 3 , 8 , 11 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. The PRISMA flow diagram is demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No additional studies were added through the manual search. Therefore, a total of 18 studies were included in the meta-analysis [ 3 , 8 , 11 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. The PRISMA flow diagram is demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 cohort studies from 2011 to 2021 were included in our meta-analysis with a total population of 12,270 patients (3460, 28.2% female) [ 3 , 8 , 11 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. There were 4, 13, and 1 studies that used an LVEF cutoff value of >50%, >40–45%, and >35% for LVEF recovery, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…В ходе проведенного исследования были получены мало ожидаемые результаты, указывающие на более выраженную структурную перестройку левых отделов сердца у больных ДКМП. Считается, что увеличение размеров ЛЖ ассоциируется с худшим про гнозом [15] и меньшей вероятностью восстановления утраченных функций сердца [16]. Крупный метаанализ, проведенный в 2019г (14939 больных c ФП и 50720 пациентов без ФП), продемонстрировал сильные связи между диаметром и объемом ЛП и неблагоприятными событиями: декомпенсацией ХСН и смертью [17].…”
Section: Discussionunclassified
“…In two recent large, retrospective analyses of patients with heart failure, 38% and 34% of patients had recovery of their EF (defined as improvement > 10%) after a waiting period of at least 6 months or 9 weeks, respectively, which is similar to the rate of recovery in our population [ 4 , 5 ]. Previous studies have identified several factors associated with EF recovery, including female sex, younger age, nonischemic cardiomyopathy, lower baseline EF, left ventricle end-diastolic volume, and tricuspid annular plane systolic excursion (TAPSE) [ 4 - 6 ]. The failure to identify any significant factor aside from initial EF in predicting recovery in this study may have been related to the small sample size.…”
Section: Discussionmentioning
confidence: 99%